2017
DOI: 10.1007/s00455-017-9826-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Laryngopharyngeal Endoscopic Esthesiometer (LPEER) for Evaluating Laryngopharyngeal Mechanosensitivity: A Validation Study in a Prospectively Recruited Cohort of Patients

Abstract: Recent studies have shown an association between alterations in laryngopharyngeal mechanosensitivity (LPMS) and dysphagia, obstructive sleep apnea, and chronic cough hypersensitivity syndrome. A previous reliability study of a new laryngopharyngeal endoscopic esthesiometer and rangefinder (LPEER) showed high intra- and inter-rater reliability; however, its accuracy has not been tested. We performed an accuracy study of the LPEER in a prospectively and consecutively recruited cohort of 118 patients at two terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, there are some limitations with the air pulse method, including device generated noise, poor stimulus reproducibility, limited stimulus range, and a lack of commercially manufactured equipment. 43 Though equipment has since been developed to address these limitations, [44][45][46] a major benefit of the touch method is that it can be performed during routine FEES exams and does not require specialized equipment. Few studies have directly compared the air pulse and touch methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limitations with the air pulse method, including device generated noise, poor stimulus reproducibility, limited stimulus range, and a lack of commercially manufactured equipment. 43 Though equipment has since been developed to address these limitations, [44][45][46] a major benefit of the touch method is that it can be performed during routine FEES exams and does not require specialized equipment. Few studies have directly compared the air pulse and touch methods.…”
Section: Discussionmentioning
confidence: 99%
“… 81 The high intra- and inter-rater reliability and accuracy of LPEER for evaluating laryngopharyngeal sensitivity have been proved. 82 , 83 Studies have shown that in patients with laryngeal irritation, the LART is slightly increased and the CRT and GRT are decreased. 81 At present, studies are focused on the application of this device in the evaluation of laryngopharyngeal sensitivity in patients with difficult swallowing, while no related studies have been conducted in patients with chronic cough.…”
Section: Evaluation Methods For Cough Sensitivitymentioning
confidence: 99%
“…Giraldo-Cadavid et al [81][82][83] designed and developed a novel laryngopharyngeal endoscopic esthesiometer and rangefinder (LPEER) composed of a high precision air pulse generator, an endoscopic laser rangefinder. The device uses endoscopic air pulses to generate pressure on the mucosa of the laryngopharyngeal tube; increasing pulse intensity triggers the laryngeal adductor reflex, cough reflex, and gag reflex.…”
Section: Chemical Stimulationmentioning
confidence: 99%